2019
DOI: 10.3390/molecules24081579
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Analysis of a Flavonol Synthase Gene from Grape Hyacinth

Abstract: Flavonols are important copigments that affect flower petal coloration. Flavonol synthase (FLS) catalyzes the conversion of dihydroflavonols to flavonols. In this study, we identified a FLS gene, MaFLS, expressed in petals of the ornamental monocot Muscari aucheri (grape hyacinth) and analyzed its spatial and temporal expression patterns. qRT-PCR analysis showed that MaFLS was predominantly expressed in the early stages of flower development. We next analyzed the in planta functions of MaFLS. Heterologous expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Total RNA was extracted from different tissues of grape hyacinth, including roots, bulbs, and leaves, and from the flowers at five developmental stages using the Total RNA Kit (Omega, Norcross, GA, USA). The five stages (S1–S5) of petals of grape hyacinth were divided according to the petal pigmentation [30] (Figure 2A). Next, 1 μg of RNA was used to synthesize cDNA by using the PrimeScript™ RT reagent Kit with gDNA Eraser (Takara Biotechnology, Dalian, China), following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted from different tissues of grape hyacinth, including roots, bulbs, and leaves, and from the flowers at five developmental stages using the Total RNA Kit (Omega, Norcross, GA, USA). The five stages (S1–S5) of petals of grape hyacinth were divided according to the petal pigmentation [30] (Figure 2A). Next, 1 μg of RNA was used to synthesize cDNA by using the PrimeScript™ RT reagent Kit with gDNA Eraser (Takara Biotechnology, Dalian, China), following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Structural genes encode anthocyanin biosynthesis enzymes directly. CHS, CHI, F3H, F3′H, DFR and ANS are structural genes in the anthocyanin synthesis pathway, which have been studied in many plants [33,34]. The regulation of these enzymes via genetic engineering can influence anthocyanin biosynthesis, thus changing flower colors or improving the variety of flowers.…”
Section: Structural Genesmentioning
confidence: 99%
“…Since the first FLS was verified in the protein extracts from irradiated parsley cells (Britsch et al ., 1981), dozens of FLS enzymes have been characterized from various plant species. Generally, there is only one FLS gene characterized from various plants (Holton et al ., 1993; Moriguchi et al ., 2002; Nielsen et al ., 2002; Toh et al ., 2013; Kim et al ., 2014; Vu et al ., 2015; Liu et al ., 2017; Park et al ., 2017; Zhou et al ., 2017; Liu et al ., 2019; Sun et al ., 2019). Gene expression analysis showed that the functional FLSs were mainly expressed in young floral buds, which did not correspond well with the disproportionately high total flavonol content in the flowers and tissues in later stages of development in some plant species (Davies et al ., 1993; Holton et al ., 1993; Nielsen et al ., 2002; Liu et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, there is only one FLS gene characterized from various plants (Holton et al ., 1993; Moriguchi et al ., 2002; Nielsen et al ., 2002; Toh et al ., 2013; Kim et al ., 2014; Vu et al ., 2015; Liu et al ., 2017; Park et al ., 2017; Zhou et al ., 2017; Liu et al ., 2019; Sun et al ., 2019). Gene expression analysis showed that the functional FLSs were mainly expressed in young floral buds, which did not correspond well with the disproportionately high total flavonol content in the flowers and tissues in later stages of development in some plant species (Davies et al ., 1993; Holton et al ., 1993; Nielsen et al ., 2002; Liu et al ., 2019). Comparatively, more FLS genes have been isolated in other plants (Downey et al ., 2003; Owens et al ., 2008a; Ferreyra et al ., 2010; Ferreyra et al ., 2012; Xu et al ., 2012; Li et al ., 2013; Akita et al ., 2017; Zeng et al ., 2017; Matsui et al ., 2018; Sun et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%